Organic fertilizer substitution optimizes aroma metabolites in Wuyi Rock tea - Huang, Shuping; Yu, Yongdong; Cui, Jilai; Luo, Zhengwei; Luo, Lanxin; Song, Chuankui; Liao, Hong (Frontiers in Plant Science, 2025)
Pleasant aroma is a distinctive character of Wuyi Rock tea, but its optimization through agricultural practices remains largely unexplored. Here, we conducted a two-year field trials in the core-region of Wuyi Rock tea production area with organic or chemical fertilizer. The results indicated that organic fertilizer significantly improves soil fertility, as indicated by increased pH and organic matter. GC-MS analysis showed that organic fertilizer obviously affects the aroma metabolites in tea leaves, with the levels of 1-Hexanol (C6H14O), 2-Ethyl-1-hexanol (C8H18O), (E,E)-2,4-Heptadienal (C7H10O), E-Nerolidol (C15H26O) and 3-octen-2-one (C8H14O) increasing by 56.55%, 104.44%, 64.39%, 64.10% and 48.10%, respectively, compared to chemical fertilizer, thereby improving its aroma quality. The correlation analysis and PLS-PM model combined with the results from ionomics and metabolomics, further elucidated that soil fertility significantly impacted the mineral nutrients in tea leaves, thereby regulating the content of volatile metabolites. Altogether, the research findings provide practical fertilizer usage guidelines for tea farmers, helping to improve the aroma quality and overall market value of tea.